Bone loss with antiepileptic drug therapy: a twin and sibling study - Shiek Ahmad, B.; Petty, S.; Gorelik, A.; O Brien, T.; Hill, Keith; Christie, J.; Sambrook, P.; Wark, J. (Springer, 2017)
© 2017 International Osteoporosis Foundation and National Osteoporosis FoundationSummary: Changes in areal bone mineral density (aBMD) and other predictors of bone loss were evaluated in 48 same-sex twin/age-matched sibling pairs discordant for antiepileptic drug (AED) use. AED users had reduced BMD at the hip regions. Prolonged AED users had greater aBMD loss, predicting a higher risk of bone fragility. Introduction: To investigate the longitudinal associations of bone mineral measures with antiepileptic drug (AED) use, including enzyme-inducing (EIAED) and non-enzyme-inducing (NEIAED) types, and other predictors of bone loss in a study of 48 same-sex twin/age-matched sibling pairs (40 female, 8 male) discordant for AED use. Methods: Using dual-energy X-ray absorptiometry (DXA), areal bone mineral density (aBMD) and content (BMC) at the hip regions, forearm, lumbar spine, and whole body were measured twice, at least 2 years apart. The mean within-pair difference (MWPD), MWPD%, and mean annual rate of aBMD change were adjusted for age, weight, and height. Predictors of bone loss were evaluated. Results: AED users, compared to non-users, at baseline and follow-up, respectively, had reduced aBMD at the total hip (MWPD% 3.8, 4.4%), femoral neck (4.7, 4.5%), and trochanter regions (4.1, 4.6%) (p < 0.05). For the whole cohort, the annual rate of change in all aBMD/BMC (p > 0.05) regions did not differ within pairs. Nevertheless, EIAED users had greater aBMD loss than non-users (n = 20 pairs) at the total hip (1.7 vs. 0.3%, p = 0.013) and whole body regions (0.7% loss vs. 0.1% BMD gain, p = 0.019), which was not found in NEIAED-discordant pairs (n = 16). AED use >20 years predicted higher aBMD loss at the forearm (p = 0.028), whole body (p = 0.010), and whole body BMC (p = 0.031). Conclusions: AED users had reduced aBMD at the hip regions. Prolonged users and EIAED users had greater aBMD loss, predicting a higher risk of bone fragility. Further prospective studies of AED effects on bone microarchitecture are needed.